A Proposed Electronic System for a Smartphone to Improve Communication Between Academics, Administrators, and Students at Palestinian Universities: Palestine Ahliya University as a Case Study: مقترح نظام إلكتروني لتطبيق هاتف ذكي لأساتذة الجامعات الفلسطينية وطلبتها لتعزيز التواصل الإداري والأكاديمي دراسة حالة: جامعة فلسطين الأهلية - Hiba Mustafa Salahat, Ahmad Mohammed Hasasneh, Sameh Nadeer Taqatqa, (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
This study has investigated the improvement of communication between students, academic and administrative departments at Palestinian universities, Palestine Ahliya University (PAU) in particular, by proposing a smartphone application. In particular, the study aimed to measure the level of administrative and academic communication provided to students and staff by the current e-services (portal and email) and traditional paper method at PAU, and thus identify their most prominent administrative and academic needs. In this paper, the descriptive-analytical method was used and a questionnaire was distributed to academics and head of administrative departments who have direct contact with university students. A random sample of the university students of different levels was selected at PAU as a case study. More precisely, 221 questionnaires were distributed, 169 were retrieved and analyzed using Google Drive. The results showed a real weakness in the communication level between the academic departments, administrative departments, and students, which shows that the current e-services at PAU are not sufficient and need to be enhanced. In particular, 82% of staff reported poor communication through the academic portal, and 70% reported poor communication via email. The rates of communication weakness of the academic gate and email for students were lower than teachers, reaching 72.2% and 67.2%, respectively. The results also showed that there is a lot of time and effort wasted by using the traditional method. All of these currently used methods led to a poor commitment to the university policy and instructions and additional workload for the administrative departments. In addition to that, the results showed the most important academic and administrative needs for students, academic and administrative departments. The most important needs were the administrative ones (83.6% for teachers and 81.4% for students), most notably, the admission and registration services followed by the needs of the Alumni and Training Unit. Ranked second were the academic needs (75.8% for teachers and 72.6% for students) which include the policy of exceptions and absence, and academic advising services. Therefore, developing a smartphone application that meets all of these needs would play an important role in bridging and activating communication between the students as well as academic and administrative departments.
Keywords: الريادة; Google Drive; النظام الإلكتروني; هاتف ذكي; جامعة فلسطين الأهلية